DAMPAK TOXIC PARENTING TERHADAP PERKEMBANGAN EMOSIONAL ANAK USIA DINI - Muyasaroh; Sumiyati (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2024)
Children's development is greatly influenced by the parenting style provided by parents. Parents with toxic parents are used to saying harsh words to their children, insulting, degrading, comparing and even forcing their wishes on their children. The method used is a qualitative library research, collecting data by searching for sources and constructing them from various sources such as books, journals and existing research. Toxic parenting itself occurs because of many things, including trauma that parents have had in the past, personal problems that parents have, inappropriate emotional control and too high expectations from parents for their children. There are several types of toxic parenting, including pageant present, namely parents who want to shape their children according to their wishes, dismissive parents, namely parents who always underestimate their children, and contemptuous parents, namely parents who often insult their children. There are many impacts resulting from toxic parent behavior. Children who experience toxic parents will have a low self-image. Parents can carry out and implement positive parenting by recognizing children's behavior, giving opportunities and trust to children, controlling their emotions and maintaining good communication with children so that children's development, especially in social and emotional terms, increases